Kesesuaian dan Daya Dukung Wisata Pesisir Tanjung Pasir dan Pulau Untung Jawa - Akrom Muflih; Achmad Fahrudin; Yusli Wardiatno (Jurnal Ilmu Pertanian Indonesia, 2015)
The objective of research was to determine the suitability and carrying capacity of Tanjung Pasir Coast and Untung Jawa Island for tourism. Research was conducted through survey descriptively and evaluative approaches to obtain primary data while secondary data also collected as supporting. The suitability of Tanjung Pasir Beach for tourism was 83.33% (highly suitable), Untung Jawa Beach 78.57 and 85.71% (highly suitable), mangrove 56.14% (suitable), but snorkeling 42.11% (not suitable) and 56.14% (suitable). Carrying capacity for tourism in the beach of Tanjung Pasir were 162 tourists/day, Untung Jawa 74 tourists/day, mangrove tourism 69 tourists/day, and snorkeling 20 tourists/day. However, the actual numbers of tourists in the region have exceeded the carrying capacity. Therefore, the control of tourists number is needed in order to match the carrying capacity of its environment as a management measure.